THE EFFECT OF THE MARKETING MIX ON SALES VOLUME AT PT SAMSUNG ELEKTRONIK INDONESIA (SAMSUNG) - Mudayat Mudayat (SEAN Institute, 2022)
This study aims to determine how influential the marketing mix (product, price, place, promo) on the sales volume of the Samsung brand, especially in Phonemart stores, the factors causing the increase and decrease are due to intense competition with many competing companies. The data of this study were obtained from a questionnaire (questionnaire) and several observations. The population in this study were 80 samples who bought Samsung mobile phones. The type of research used is quantitative, sampling using the Slovin formula with Data Management Techniques used are validity and reliability tests, classical assumption tests, multiple regression, and hypothesis testing (F test and t test). The results of the analysis show that simultaneously the marketing mix has an effect on sales volume. Partially, product and place affect sales volume. The place variable is the dominant variable affecting the sales volume of the Samsung brand.